Zrnate stročnice v prehrani rejnih živali (University of Maribor Press, 2022)
Grain Legumes in Nutrition of Farm Animals. The sources and needs of protein feeds for farm animals in the world, in Europe and in Slovenia are presented in the publication. In addition, the specificities of protein digestion, the limitations of using different protein feeds in the diet, the composition of protein feeds and their energy and protein value for monogastric animals and ruminants are described. Emphasis is placed on grain legumes and oilseeds and their products. We also present examples of complete feed mixtures for poultry and pigs that may contain different locally grown grain legumes. A special chapter is devoted to the possibility of including heat-treated and unprocessed whole soybeans, soybean cakes and meals in diets for dairy cows and beef cattle. The procedures and effects of heat treatment of soybeans, soybean cakes and meals are also described. We conclude the publication with a description of Slovenian best practices in the use of home-grown grain legumes and their products as a local source of protein.